ANALYSIS OF THE INFLUENCE OF BRAND IMAGE, PRICE AND SERVICE QUALITY ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE - Rachman, Avivatur; Fatimah, Feti; Tyas, Wenny Murtalining (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
This study aims to analyze the influence of brand image, price and service quality on customer loyalty with customer satisfaction as an intervening variable in Donat-Roti Ciliwung Pagah Jember Branch customers. The quantitative approach method was used in this study. Examining was done by purposive sampling, the number of samples in this study was 105 respondents. The analysis used in this study used a variance-based SEM test or Partial Least Square (SEM-PLS) with the Warp PLS 7.0 program. The results of the study prove, brand image has a positive and significant effect on customer satisfaction, brand price has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction, brand image has a positive and significant effect on customer loyalty, price has a positive and significant effect on customer loyalty, service quality has a positive and significant effect on customer loyalty,  Customer satisfaction has a positive and significant effect on customer loyalty, there is an indirect influence both from the variables of brand image, price and service quality on customer loyalty through intervening variables of customer satisfaction. With the value of indirect influence is small than the direct influence.